2023
DOI: 10.1177/23259671231168892
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Schenck KD I Classification in Patients With Documented Tibiofemoral Knee Dislocations: A Multicenter Retrospective Case Series

Abstract: Background: Acute tibiofemoral knee dislocations (KDs) with a single cruciate ligament remaining intact are rare and can be classified as Schenck KD I. The inclusion of multiligament knee injuries (MLKIs) has contributed to a recent surge in Schenck KD I prevalence and has convoluted the original definition of the classification. Purpose: To (1) report on a series of true Schenck KD I injuries with radiologically confirmed tibiofemoral dislocation and (2) introduce suffix modifications to further subclassify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…2,22 Given that MLKI and KD are often intertwined, it is becoming even more apparent that 2 distinct entities exist along the progressive spectrum of ligamentous knee injuries. 8,20,23 Sustaining a traumatic KD with radiographic evidence of tibiofemoral disarticulation or clinical documentation of a manual reduction of a tibiofemoral KD has been shown by our multi-institutional data to be associated with a poorer clinical outcome and reduced activity capacity at a mean of 6.5 years after injury. Documented KDs likely represent a greater insult to the soft tissue envelope than a nondislocated 3-ligament knee injury.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…2,22 Given that MLKI and KD are often intertwined, it is becoming even more apparent that 2 distinct entities exist along the progressive spectrum of ligamentous knee injuries. 8,20,23 Sustaining a traumatic KD with radiographic evidence of tibiofemoral disarticulation or clinical documentation of a manual reduction of a tibiofemoral KD has been shown by our multi-institutional data to be associated with a poorer clinical outcome and reduced activity capacity at a mean of 6.5 years after injury. Documented KDs likely represent a greater insult to the soft tissue envelope than a nondislocated 3-ligament knee injury.…”
Section: Discussionmentioning
confidence: 66%
“…4,14,28 Recent studies have shown a higher risk of neurovascular injury in the documented KD as well as misappropriation of the term ''knee dislocation'' for nondislocated MLKIs. 8,14 While it has been stated that up to 50% of MLKIs may have ''spontaneously reduced'' before presentation, 29 this represents a presumptive diagnosis to an entity that has never been documented and has spawned a phrase that may be misused when describing an MLKI without objective evidence of disarticulation. MLKI and KD are often used interchangeably, in spite of the awareness that the latter describes a soft tissue injury of greater severity.…”
mentioning
confidence: 99%
See 3 more Smart Citations